PENERAPAN BAURAN PROMOSI DALAM PENYELENGGARAAN LASCARYA TEGALLALANG FESTIVAL - Nyoman Sri Manik Parasari; Ni Putu Yunita Anggreswari; Anak Agung Istri Agung Maheswari; I Putu Dharmawan Pradhana (LPSDI Bina Patria, 2022)
The recovery of tourism can run if there are activities that develop and are sustainable, the fact is that many business sectors have stopped and gone out of business during the Covid-19 pandemic. Seeing from this phenomenon, tourism is the wheel of life rotation of the Balinese people in general. One of the impacts affected by the pandemic is in Gianyar, especially Tegallalang Village. Starting from the concern of the youth generation of Tegallalang Village towards the development of tourist villages, by having existing natural resources and human resources, of course there are many activities that can can be carried out to revive tourists' interest in coming to visit Tegallalang Village. Lascarya Tegallalang Festival is held to help the problems faced by the people of Tegallalang Village. The problem has an impact on various fields such as socio-cultural, arts, tourism villages, public health and welfare. This study uses qualitative methods to determine the phenomena that occur in Tegalalang Village. The data collection stage uses in-depth interviews, by conducting direct questions and answers with the informants who have been selected, namely the Chairman of the Committee Lascarya Tegallalang Festival, Community Leaders, and the Inter-Youth Communication Forum in Tegallalang Village. Based on the results of interviews conducted by researchers, it can be said that with the promotional mix applied in the Lascarya Tegalallang Festival activities through social media: instagram, youtube, RRI radio communication facilities and community leaders.